Studi Deskriptif mengenai Coping Stress pada Eks-Pasukan Perdamaian Garuda Pasca Bertugas di Negara Kongo - Adiputra, Fendy; Victoriana, Evany; Adelina, Ira (Zenit, 2013)
This research is conducted with the aim to find a description of the coping stress strategies used by the ex-post duty of Garuda Peacekeepers in the Democratic Republic of The Congo. The design used in this study is a descriptive research using a questionnaire. The study involves 80 respondentsdrawn from a population of 180 people.Measuring instruments used are the Ways of Coping Questionnaire (WCQ) developed by Lazarus and Folkman (1984,) which has been modified by the researcher. The questionnaire consists of 43 items with each item validity between 0.303 to 0.640 and the degree of reliability of 0.790. From the research,it is found out that 46.25% of Garuda peacekeepers post duty in the Democratic Republic of The Congo use both types of stress copingstrategies. A total of 28.75% uses stress coping strategies that focus on problem and as much as 25% uses coping strategies focused on emotion. Suggestions for further research is to conduct research on the effectiveness of coping stress strategies in order to obtain an idea of the effective stress coping strategies for the soldier in charge of the country, especially after duty of the Congo. The researchercan also do research on how strong the contribution of degree of stress, work experience in their influence on the use of stress coping strategies.Keywords: coping stress, garuda peacekeepers